Toward longitudinal studies of hemodynamically induced vessel wall remodeling. Issue 11 (November 2018) - Bozzetto, Michela; Brambilla, Paolo; Rota, Stefano; Ene-Iordache, Bogdan; Sironi, Sandro; Remuzzi, Giuseppe; Remuzzi, Andrea
Introduction: Autogenous arteriovenous fistula is the preferred vascular access for hemodialysis, but it has high rates of non-maturation and early failure due to vascular stenosis. Convincing evidence supports a key role of local hemodynamics in vascular remodeling, suggesting that unsteady and disturbed flow conditions may be related to stenosis formation in arteriovenous fistula. The purpose of our study was to explore the feasibility of coupling contrast-free magnetic resonance imaging and computational fluid dynamics in longitudinal studies to identify the role of local hemodynamic changes over time in inducing vessel wall remodeling in arteriovenous fistula. Methods: We acquired contrast-free magnetic resonance imaging of arm vasculature at 1 week and 6 weeks after arteriovenous fistula creation in a 72-year-old patient. We then generated three-dimensional models and evaluated lumen cross-sectional area of arteriovenous fistula limbs. We performed high-resolution computational fluid dynamics to evaluate changes in local hemodynamics over time. Results: Our contrast-free magnetic resonance imaging protocol provided good quality images in a short scan duration. We observed a homogeneous dilatation in the proximal artery, while there was a more pronounced lumen dilatation in the venous outflow as compared to a limited dilatation in the juxta-anastomotic vein. Furthermore, we observed a slight stabilization of the flow pattern over time, suggesting that vascular outward remodeling accommodates the flow to a more helicoidally phenotype. Conclusion: Coupling contrast-free magnetic resonance imaging and high-resolution computational fluid dynamics represents a promising approach to shed more light in the mechanisms of vascular remodeling and can be used for prospective clinical investigations aimed at identifying critical hemodynamic factors contributing to arteriovenous fistula failure.